Comparative analysis and performance of two predictive fade detection schemes for Ka-band fade countermeasures. - Gremont, B. (IEEE Journal on selected areas in communications)
The design of Ka-band satellite fade countermeasure (FCM) systems is conditioned by the detection/prediction algorithm to be included within practical DSP-based FCM controllers. It depends upon the ability of systems to efficiently integrate the dynamic and stochastic nature of the Ka-band fading process which is dominated by rain attenuation and amplitude scintillation. The paper analyzes the modeling and statistical performance of two predictive fade detection algorithms. Prediction is introduced as a way to minimize the impact of the finite response time on the BER/throughput of practical FCM systems. Both fixed (FDM) and variable (VDM) detection margin strategies are introduced and compared in terms of their margin requirements, FCM utilization factor, and channel capacity utilization. The VDM is shown to be more efficient than its fixed counterpart. The long-term BER availability and average user data throughput of a VDM/fixed-FEC/adaptive transmission rate FCM are then evaluated for a typical low-power low-rate Ka-band in-bound VSAT link